The effects of tamarindus indica seed extract as anti-snake venom against ophiophagus hannah venom in mice - Nur Farhanah binti Azmi
Snakebite is one of the public health problems in many developing and poor tropical countries. The existing snake antivenoms have limited supply, are expensive, and susceptible to many adverse effects. Herbal medicines are option in these countries and Tamarindus indica is one of the plants that was used to treat snake envenomation. The venom used in this study was Ophiophagus hannah venom. In this study, phytochemical screening of T. indica seed extract (TSE) was done to screen for saponins, alkaloids, flavonoids, anthraquinone derivatives, phenolics, tannins, terpenoids, triterpenoids, steroids and essential oil. Phytochemical screening showed TSE contains phenolics and tannins, with total phenolic content of 72.644 ± 4.187 mg GAE/g extract. The inhibition of lethality study of Institute of Cancer Research (ICR) mice treated with serial doses of TSE 15 mg/20 g body weight after envenomation with O. hannah venom showed the mice survival rate increased when the shorter treatment time interval between envenomation and the TSE treatment. 15 minutes treatment interval recorded the highest survival rate at 80%, followed by 30 minutes and 60 minutes treatment interval with 67% and 20% survival rate respectively. In the histological analysis, it showed that TSE was able to prevent further damage to skin, liver and kidney of envenomed mice. These results demonstrate that T. indica has the potential as anti-snake venom against O. hannah.